Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions (vol 5, pg 1251, 2015) - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2016)
Correction for ‘Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions’ by Najrul Hussain et al., Catal. Sci. Technol., 2015, 5, 1251–1260.